DIGITIZATION OF HISTORICAL MUSEOLOGY LABORATORY (E-MUSEUM) BASED ON QR CODE AS AN INNOVATIVE HISTORICAL RESOURCE - Putra, Candra Kurnia; Sulistyo , Wahyu Djoko; Wahyuda, Sya'fa Nabila Kurnia (JP (Jurnal Pendidikan) : Teori dan Praktik, 2024)
Technology transformation from Revolution 4.0 to Society 5.0, where technology is increasingly integrated with human life. Education is the key in developing innovative human resources. In the era of Society 5.0, with the rapid development of technology, it is necessary to transform from manual to digital learning resources. Based on the importance of this, the purpose of this research is to digitize historical sources in a Qr Code-based museology laboratory and test their effectiveness. The use of learning resources, especially in the form of a museology laboratory with a Qr Code, is an innovative way to enhance history learning. In this study, the method used was the Research and Development (R&D) ADDIE model. This model has 5 stages consisting of analyzing, designing, developing, implementing and evaluating. The focus of the research object was conducted at the Department of History, Faculty of Social Sciences, State University of Malang, East Java Province. The trial results show that it is very effective in 86% points to improve the quality of history learning. Through the results of technology and education collaboration in the Society 5.0 era, practical implementation emerged in the form of a Qr Code-based E-Museum